2020
DOI: 10.15406/jdmdc.2020.07.00211
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown and diabetes–what actually happened?

Abstract: Proper glycemic control is important in diabetes management, particularly during the COVID-19 pandemic. Lockdown restrictions led to increased stress and hampered the daily living of many individuals. The evidence available on the impact of the pandemic on diabetes management is predominantly from cities and through online mode. Teleconsultation is an option to be made available to rural areas as well. During the lockdown, reaching out to the doctor and procurement of medications was a huge task for the underp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A recent meta-analysis confirmed that there is a concomitantly lower level of awareness (52.7%), treatment (45.3%), and glycemic control (36.7%) prevalent in diabetic population under antidiabetic treatment in Nepal [3]. Lockdown has shown a negative impact on glycemic control and worsened the complication due to DM [4]. Nepal had a lockdown approximately for a period of 4 months as the COVID-19 cases were on upsurge [2].…”
Section: Seeking Laboratory Investigations By Diabetic Patients During Covid-19 Lockdown Of Eastern Nepalmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent meta-analysis confirmed that there is a concomitantly lower level of awareness (52.7%), treatment (45.3%), and glycemic control (36.7%) prevalent in diabetic population under antidiabetic treatment in Nepal [3]. Lockdown has shown a negative impact on glycemic control and worsened the complication due to DM [4]. Nepal had a lockdown approximately for a period of 4 months as the COVID-19 cases were on upsurge [2].…”
Section: Seeking Laboratory Investigations By Diabetic Patients During Covid-19 Lockdown Of Eastern Nepalmentioning
confidence: 99%
“…The nation-wide lockdown is a crucial step to prevent the transmission of infection during the pandemic [1]. But there is a high possibility of the lockdown to affect the chronic disease patients like DM in terms of deterioration of glycemic control and disease-associated risk [4]. Also, confinement in the specific space, erratic diet, increased stress, restriction in continuing the physical activities could be the other possibilities for the poor glycemic control [4].…”
Section: Seeking Laboratory Investigations By Diabetic Patients During Covid-19 Lockdown Of Eastern Nepalmentioning
confidence: 99%
See 2 more Smart Citations